Indonesia's South-South and Triangular Cooperation (SSTC) as the Future of Diplomacy for World Solidarity to Overcome the COVID-19 Pandemic - Muhammad Ridha Iswardhana (Institute of International Studies, 2020)
The COVID-19 pandemic that started in China has expanded throughout the world. As a result, all countries have to face various challenges due to the Corona Virus. It does not only threaten the health, but also the economy, social, culture and politics of almost all countries. The worst conditions are faced by many developing countries that are unable to overcome the various adverse effects caused by the virus.However, currently, there is no world leadership yet capable to overcome the Corona Virus problem for all countries. Treatment tends to be domestic and unilateral. To solve the pandemic, there is a south-south cooperation framework known as SSTC. Collaboration and partnerships between southern countries are important because more developing countries are facing the impact of the virus. Indonesia as one of the successful actors operating SSTC since 2010 can use this framework of cooperation as solidarity with other southern countries.In this article, a descriptive qualitative approach is used to explain and analyze the conditions that occur concerning the theories. The author uses the theory of Soft Power and International Assistance, aims to explain how Indonesia's diplomacy policy through the SSTC is the finding that Indonesia conducted a series of assistance and training to various countries during the Pandemic. This paper contributes to showing Indonesia's consistent policy and position to overcoming COVID-19 towards several developing countries. However, Indonesia needs consistenantyto increase its role in handling the Corona Virus in various developing countries.